Frontline Science: Blood-circulating leukocytes fail to infiltrate the spinal cord parenchyma after spared nerve injury. Issue 3 (31st May 2019) - Guimarães, Rafaela M; Davoli-Ferreira, Marcela; Fonseca, Miriam M; Damasceno, Luis Eduardo A; Santa-Cecilia, Flavia V; Kusuda, Ricardo; Menezes, Gustavo B; Cunha, Fernando Q; Alves-Filho, Jose C; Cunha, Thiago M
Abstract: The development of neuropathic pain after peripheral nerve injury involves neuroimmune–glial interactions in the spinal cord. However, whether the development of neuropathic pain depends on the infiltration of peripheral immune cells, such as monocytes, into the spinal cord parenchyma after peripheral nerve damage remains unclear. Here, we used a combination of different techniques such as transgenic reporter mouse ( Cx3cr1 GFP/+ and Ccr2 RFP/+ mice), bone marrow chimeric mice, and parabiosis to investigate this issue in spared nerve injury (SNI) model. Herein, we provided robust evidence that, although microglial cells are activated/proliferate at the dorsal horn of the spinal cord after SNI, peripheral hematopoietic cells (including monocytes) are not able to infiltrate into the spinal cord parenchyma. Furthermore, there was no evidence of CCR2 expression in intrinsic cells of the spinal cord. However, microglial cells activation/proliferation in the spinal cord and mechanical allodynia after SNI were reduced in Ccr2 -deficient mice. These results suggest that blood-circulating leukocytes cells are not able to infiltrate the spinal cord parenchyma after distal peripheral nerve injury. Nevertheless, they indicate that CCR2-expressing cells might be indirectly regulating microglia activation/proliferation in the spinal cord after SNI. In conclusion, our study supports that CCR2 inhibition could be explored as an interventional approach to reduce microglia activation and consequently neuropathic pain development after peripheral nerve injury. Graphical Abstract: Provides evidence that blood-circulating leukocytes fail to infiltrate the spinal cord parenchyma after a distal peripheral nerve injury.